The Design of an Inquiry-Based Learning Model Integrating Mangrove Local Wisdom in Primary School Social Studies to Foster Social Attitudes - Laelia Nurpratiwiningsih; Rusdarti Rusdarti; Joko Widodo; Tjaturahono Budi Sanjoto (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to design an inquiry-based learning model that integrates local wisdom about mangroves into primary school Social Studies to foster students' social attitudes. Employing a Research and Development approach with the 4D model (define, design, develop, disseminate), this research involved 6 primary school teachers and 60 fifth-grade students from coastal schools in Brebes Regency, Indonesia. Data were collected through needs analysis, expert validation, observations, interviews, and questionnaires. The resulting model systematically integrates seven-stage inquiry syntax with mangrove socio-ecological contexts, explicitly oriented toward developing cooperation, empathy, and responsibility. Expert validation by three specialists yielded an average feasibility score of 4.35 out of 5, indicating a very high level of validity. Limited trials revealed measurable improvements in students' social attitudes: cooperation increased by 18%, responsibility by 17%, and empathy by 15%. Qualitative data confirmed enhanced student engagement, collaboration, and environmental awareness. Teachers reported that the model effectively connected learning with students' real-life contexts, although they acknowledged the need for further training and assistance. This study contributes theoretically to contextual Social Studies pedagogy and, in practice, offers a sustainable instructional model for character education in coastal primary schools. The novelty lies in the systematic integration of inquiry-based learning, local mangrove wisdom, and explicit assessment of social attitudes within a single instructional design. Keywords: character education, inquiry-based learning, mangrove local wisdom, primary school social studies, social attitudes